Acoustic abundance estimation of the Icelandic stock of capelin : 1978-1982 - Vilhjálmsson, Hjálmar; Reynisson, Páll; Hamre, Johannes; Røttingen, Ingolf (ICES, 1982)
ICES, Symposium on Fisheries Acoustics, Bergen, 1982, No. 21 During the period October 1978 - february 1982 several abundance estimates and yearclass composition of the Icelandic capelin stock were obtained by acoustic methods. Surveying has been carried out in July-Agust, September, October, November as well as in January-February and on one occasion in early March. It has been found that consistent abundance estimates of the older yearclasses (excluding 0- and 1-group fish) can be obtained in autumn and winter by this method while the fish still occupy deep water areas off NW-, N-, NE- and E-Iceland. Due to drift ice and periods of bad weather it has at times proved necessary to wait or repeat surveys for these reasons. This paper describes and discusses the abundance estimates obtained during the above period. They have been used for management purposes.